The struggle against neoliberal austerity and the survival of the European project - Misir, Timothy L. (2014)
This paper takes stock of the reality of the European Union (EU) in the 21st century as ongoing European integration appears to have resulted in a disconnect between the governing elites and the masses as politics has been subverted in favour of economic interests. In the wake of the global financial crisis and the current sovereign debt crisis, counter-hegemonic forces and political counter currents within the EU have begun to surface with their struggle against neoliberal austerity. This paper argues that far from being anti-European, these actors may be the key to the survival of the European project and its social goals, and that these movements may contribute to the reduction of the democratic deficit in the EU and bring about a new social order. What is significant about these movements is their autonomous and cosmopolitan nature and their distance from partisan politics. Though largely not coordinated, these movements have gained momentum and spread across the continent. While initially confined to national arenas, there is a growing European dimension to these movements as actors try to shape an alternative agenda toward a EU that prioritises the social dimension. As the EU moves toward a postnational and post-Fordist stage, this paper also looks at the emerging political landscape being shaped by new forms of collective organisation in the EU, and the reordering of political hierarchy shaped by transnationalisation and global networking.